2018
DOI: 10.3390/su10030822
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Graphene Nanosheets on Rheology, Microstructure, Strength Development and Self-Sensing Properties of Cement Based Composites

Abstract: In this research, Graphene oxide (GO), prepared by modified hammer method, is characterized using X-ray Diffraction (XRD), Fourier Transform Infrared (FT-IR) Spectrometry and Raman spectra. The dispersion efficiency of GO in aqueous solution is examined by Ultraviolet-visible spectroscopy and it is found that GO sheets are well dispersed. Thereafter, rheological properties, flow diameter, hardened density, compressive strength and electrical properties of GO based cement composite are investigated by incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 51 publications
(77 reference statements)
3
22
0
1
Order By: Relevance
“…This is due to the increase of the high density C-S-H content and the creation of new intercalated BNP/C-S-H nanocomposites with higher density. This is consistent with Rehman et al [24] findings where they have shown that the decrease in the mass loss of GO cementitious composites is attributed to both the bonding of C-S-H with the GO sheets and the increase of the C-S-H content. In this case, the GO sheets tend to increase the amount of C-S-H product, thereby filling the pores in the matrix resulting in less amount of water available for evaporation [24].…”
Section: Influence Of Bnps On the Degree Of Hydration Of Cementitioussupporting
confidence: 92%
“…This is due to the increase of the high density C-S-H content and the creation of new intercalated BNP/C-S-H nanocomposites with higher density. This is consistent with Rehman et al [24] findings where they have shown that the decrease in the mass loss of GO cementitious composites is attributed to both the bonding of C-S-H with the GO sheets and the increase of the C-S-H content. In this case, the GO sheets tend to increase the amount of C-S-H product, thereby filling the pores in the matrix resulting in less amount of water available for evaporation [24].…”
Section: Influence Of Bnps On the Degree Of Hydration Of Cementitioussupporting
confidence: 92%
“…Significantly this conjoining of enormous oxygen-containing groups makes GO hydrophilic and highly stable in polar solvents [ 50 ]. Additionally, the appearance of one strong peak at 2350 cm −1 for both graphite and GO is attributed to the O=C=O stretching of gaseous CO 2 absorbed by the material surface [ 51 , 52 ]. The thermal stability of graphite and GO were investigated by TGA.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the presence of sheets of 0.05 wt% oxidized graphene in cement leads to an increase in compressive strength and exural strength of the material by 15-33 and 41-59%, respectively. [37][38][39] However, it is not known yet if there is any study of nanocarbon species inclusion effect on the rheological properties of nano-and submicron powders. We carry out comparative research of the nanopowders of a graphenecontaining composite and pure zirconia obtained from the same sol as a composite.…”
Section: Introductionmentioning
confidence: 99%